Aplikasi Akad Kafalah Dalam Pembiayaan Dana Talangan Haji di BMT UGT Nusantara Cabang Surabaya - Safira Aulia Amirullah (Jurnal Keislaman, 2023)
One of the activities of Non-Bank Islamic Financial Institutions or also known as BMT (Bait al-mal wa al-tamwil) is channeling funds in the form of financing. Any financing based on the principles of Islamic Financial Institutions provided by BMT contains benefits, including the financing of Hajj bailouts. The advantage of this financing is that the process is fast and the requirements are easy. By way of financing haj bailout funds at the BMT UGT Nusantara Surabaya Branch, you can pay installments for an automatic debit account or available at each office, the installment service is automatically deducted from the debit account, which is possible to do in all service offices of the BMT UGT Nusantara Surabaya Branch. Therefore, the researcher intends to analyze how to apply the kafalah contract in financing haj bailouts for BMTs. The method used in this study was to conduct field research using interview techniques. The results of the study concluded that in the contract that underlies the kafalah in financing the haj bailout there are benefits for people who want to go on pilgrimage but are still lacking in funds. So this kafalah contract aims to help the community in financing the pilgrimage in the form of bailout funds.